PENGARUH GAYA MENGAJAR GURU, MEDIA PEMBELAJARAN, DUKUNGAN TEMAN SEBAYA, LINGKUNGAN KELUARGA TERHADAP MINAT BELAJAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning media, peer support, and family environment on the learning interest of class X Accounting students at SMK Negeri 1 Sungai Penuh in the 2024/2025 academic year, both partially and simultaneously. This study used a quantitative approach with a population of 91 students, who were also sampled through a total sampling technique. Data analysis used multiple linear regression, the coefficient of determination (R²), and the T and F tests, assisted by Eviews12 software. The results showed: 1) Teacher teaching style (X1) had a significant effect on learning interest (Y) with a coefficient of 0.260 and a calculated t of 3.489 > ttable 1.662. 2) Learning media (X2) had a significant effect (coefficient 0.319; calculated t 4.009). 3) Peer support (X3) had a significant effect (coefficient 0.375; calculated t 3.119). 4) Family environment (X4) also had a significant effect (coefficient 0.234; t-test 2.415). 5) All four variables simultaneously influenced learning interest, with F-test 13.01 > F-table 2.48.